Preoperative prostate health index predicts adverse pathology and Gleason score upgrading after radical prostatectomy for prostate cancer - Novak, Vojtech; Vesely, Stepan; Luksanová, Hana; Prusa, Richard; Capoun, Otakar; Fiala, Vojtech; Dolejsová, Olga; Sedlacková, Hana; Kucera, Radek; Stejskal, Jiri; Zalesky, Miroslav; Babjuk, Marko (BMC urology, 2020)
BACKGROUND: We aimed to explore the utility of prostate specific antigen (PSA) isoform [- 2] proPSA and its derivatives for prediction of pathological outcome after radical prostatectomy (RP). METHODS: Preoperative blood samples were prospectively and consecutivelyanalyzed from 472 patients treated with RP for clinically localized prostate cancerat four medical centers. Measured parameters were PSA, free PSA (fPSA), fPSA/PSA ratio, [- 2] proPSA (p2PSA), p2PSA/fPSA ratio and Prostate Health Index (PHI)(p2PSA/fPSA)*√PSA]. Logistic regression models were fitted to determine the accuracy of markers for prediction of pathological Gleason score (GS) ≥7, Gleason score upgrading, extracapsular extension of the tumor (pT3) and the presence of positive surgical margin (PSM). The accuracy of predictive models was compared using area under the receiver operating curve (AUC). RESULTS: Of 472 patients undergoing RP, 339 (72%) were found to have pathologic GS ≥ 7, out of them 178 (53%) experienced an upgrade from their preoperative GS = 6. The findings of pT3 and PSM were present in 132 (28%) and 133 (28%) cases, respectively. At univariable analysis of all the preoperative parameters, PHI was the most accurate predictor of pathological GS ≥7 (OR 1.02, 95% CI 1.01-1.03, p<0.001), GS upgrading (OR 1.02, 95% CI 1.01-1.03, p<0.003), pT3 disease (OR 1.01, 95% CI 1.00-1.02, p<0.007) and the presence of PSM (OR 1.01, 95% CI 1.00-1.02, p<0.002). Adding of PHI into the base multivariable model increased significantly the accuracy for prediction of pathological GS by 4.4% to AUC = 66.6 (p = 0.015) and GS upgrading by 5.0% to AUC = 65.9 (p = 0.025), respectively. CONCLUSIONS: Preoperative PHI levels may contribute significantly to prediction of prostate cancer aggressiveness and expansion of the tumor detected at final pathology.
Keywords: Male; Neoplasm Grading; předoperační období; Prostatic Neoplasms; Aged; Prospective Studies; mužské pohlaví; senioři; prostatektomie; prostatický specifický antigen; lidé; stupeň nádoru; Humans; nádory prostaty; prediktivní hodnota testů; Preoperative Period; Prostatectomy; lidé středního věku; Predictive Value of Tests; Prostate-Specific Antigen; Middle Aged; prospektivní studie